Bulk sensitive angle-resolved photoelectron spectroscopy on Nd(O, F)BiS2. (January 2016) - Terashima, K; Sonoyama, J; Sunagawa, M; Fujiwara, H; Nagayama, T; Muro, T; Nagao, M; Watauchi, S; Tanaka, I; Okazaki, H; Takano, Y; Mizuguchi, Y; et al.
Abstract: Bulk electronic structure of novel layered superconductor Nd(O, F)BiS2 was studied by using soft x-ray angle-resolved photoelectron spectroscopy (ARPES). Electron-like Fermi surface centered at the X(R) point was observed, consistent with earlier ARPES reports on surface-sensitive VUV light source. Based on the comparison of the electronic structure between Nd(O, F)BiS2 and La(O, F)BiS2, we discuss possible important factors for the superconductivity in this series of material.